Analisis Faktor yang Mempengaruhi Kepatuhan Penerapan Kewaspadaan Standar pada Dokter Gigi Muda - Indah Fasha Palingga; Misnaniarti Misnaniarti; Haerawati Haerawati (Jurnal Kesehatan, 2020)
As dental health professionals, dentists have an obligation, ethical responsibility, and moral duty to ensure that they must obey standard precaution procedures to prevent the transmission of infectious diseases. This study aims to analyze associated factors affecting compliance to implementing standard precautions on a dental clinical student in Dental Hospital of South Sumatera Province. This was a cross-sectional study which was conducted in the Dental Hospital of South Sumatera Province. All clinical students becoming samples who are taken by total sampling (n=113). The data were obtained from the respondent who had filled out the questionnaires. Data were analyzed by chi-square test and binary logistic. The result obtained that 79,6% of dental clinical students adhered to standard precautions. Knowledge, attitude, work climate, leadership management support, facilities, training, and obstacles were found to be statistically significant in the chi-square test (p-value<0,05). A binary logistic test showed leadership management support as dominant variable that affecting compliance in standard precautions (p-value=0,0008), OR=5,336 (95%CI:1,561-18,242). As the key of management support, the leader is not only as a policymaker but also as a mentor about technical and evaluation instructions regarding standard precautions.